Effect of Applying Compost Tea Through Leaves and Soil on Soil P availability and P Uptake of Maize (Zea mays L.) at Alfisol Jatikerto Kab. Malang - Nanik Susilowati (Contributions of Central Research Institute for Agriculture, 2023)
This study aims to determine the effect of the compost application on P availability in Alfisols and to compare the compost application through leaves and soil to the P uptake of corn plants. The low availability of P in Alfisol is due to the bond with Ca to form tricalcium phosphate which is difficult to dissolve. One effort that can be done to overcome the lack of P in Alfisols is the addition of organic matter to the soil, both from plants and animals. The final process of decomposition of organic matter produces humic and fulvic acid compounds which can increase the availability of P. Compost tea is the result of a solution of washing nutrients and extracts of bacteria, fungi, protozoa and nematodes from compost. Compost tea can be given in two ways, namely by spraying it through the leaves and giving it to the soil through the leaves and the soil against the P uptake of corn plants. Compost tea is made using the Bubbler method. Before being applied, the compost must be diluted with distilled water (1:1 ratio) to reduce the concentration. The experimental design used in this study was a completely randomized design with 7 treatments and 3 replications with the following types of treatment: CT0 (control); CT1 (soil + compost tea 130 ml/plant equivalent to 50 l/100 m2); CT2 (soil + compost tea 250 ml/plant equivalent to 100 l/100m2 ); CT3 (soil + compost tea 400 ml/plant equivalent to 150 l/100 m2); CT4 (soil + compost tea 60 ml/plant equivalent to 25 l/100 m2); CT5 (soil + compost tea 130 ml/plant equivalent to 50 l/100 m2); CT6 (soil + compost tea 200 ml/plant equivalent to 75 l/100 m2); The results showed that the application of compost tea through the leaves and soil had a significant effect on the difference in available-P levels. Application of the compost through the leaves increased plant height, number of leaves, plant dry weight and P uptake. There was a positive correlation (r=0.386) which showed that increasing available P levels in the soil would increase plant P uptake.